Protein Effects on Surfactant Adsorption Suggest the Dominant Mode of Surfactant‐Mediated Stabilization of Protein. Issue 5 (1st March 2014) - Kim, Hyojin Lee; Mcauley, Arnold; Mcguire, Joseph
<x xml:space="preserve">Abstract</x> Surfactants stabilize proteins through two major mechanisms: (1) their preferential location at nearby interfaces, in this way precluding protein adsorption; and/or (2) their association with protein into "complexes" that prevent proteins from interacting with surfaces as well as each other. However, selection of surfactants for protein stabilization currently is not typically made with benefit of any quantitative, predictive information to ensure that either mechanism will be enforced. We compared surface tension depression by poloxamer 188, polysorbate (PS) 80, and PS 20 in the presence and absence of lysozyme or a recombinant protein. The kinetic results were interpreted with reference to a mechanism for surfactant adsorption governed by the formation of a rate‐limiting structural intermediate (i.e., an "activated complex") composed of surfactant and protein. The presence of protein was seen to increase the rate of surfactant adsorption in relation to surfactant acting alone for the PSs, with very little change in kinetics owing to protein in the case of poloxamer 188. A simple thermodynamic analysis indicated the presence of protein caused a reduction in ΔG for the surfactant adsorption process, deriving entirely from a reduction in ΔH. Thus, protein likely accelerates the adsorption of these surfactants by disrupting their self‐associations, increasing the concentration of surfactant monomers near the interface. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:1337–1345, 2014